2020
DOI: 10.1016/j.ijid.2020.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and pharmacokinetics of colistimethate sodium and colistin in critically ill patients in an Indian hospital with high endemic rates of multidrug-resistant Gram-negative bacterial infections: A prospective observational study

Abstract: Background: Safe and effective use of colistin requires robust pharmacokinetic (PK) and pharmacodynamic (PD) data to guide dosing. Aim: To evaluate the pharmacokinetics of colistimethate sodium and colistin in critically ill patients and correlate with clinical efficacy and renal function. Materials and Methods: Twenty critically ill adult patients with colistin-susceptible multidrug-resistant (MDR) infections and normal renal function treated with intravenous colistimethate sodiumat a 9 million units (270 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…A total of nine studies reported a maximum concentration (C max ) value of CMS and/or colistin after single-dose intravenous administration of CMS [2,3,5,[9][10][11][12]21,22]. Of the reported articles, five studies reported C max values of CMS and/or colistin after application of a loading dose [2,3,5,10,22]. In the single-dose study by Karvanen et al [21], patients receiving 2 MIU of CMS reported CMS C max value of 6.9 mg/L.…”
Section: Concentration Of Cms and Colistin In Plasma After Cms Administrationmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of nine studies reported a maximum concentration (C max ) value of CMS and/or colistin after single-dose intravenous administration of CMS [2,3,5,[9][10][11][12]21,22]. Of the reported articles, five studies reported C max values of CMS and/or colistin after application of a loading dose [2,3,5,10,22]. In the single-dose study by Karvanen et al [21], patients receiving 2 MIU of CMS reported CMS C max value of 6.9 mg/L.…”
Section: Concentration Of Cms and Colistin In Plasma After Cms Administrationmentioning
confidence: 99%
“…Colistin’s pharmacokinetics and clinical application have been studied extensively in the past. Unfortunately, studies have found inter- and intra-individual variability in the pharmacokinetics of colistin, resulting in extremely varied plasma concentrations following the same dosage schedule [ 2 , 3 , 4 , 5 ]. In vivo, CMS has complex pharmacokinetics and variable bioconversion, particularly in patients with varying degrees of renal function [ 2 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The available guidelines highlight the need for a mandatory loading dose on the initiation of polymyxins to ensure that optimal steady state concentrations are attained as early as possible [ 9 , 24 ]. A recent colistin pharmacokinetic study from India highlighted that decreased steady state concentrations correlated with lower clinical efficacy [ 25 ]. However, the practice of an appropriate loading dose was extremely low in our setting.…”
Section: Discussionmentioning
confidence: 99%
“…Recognising the gap in local population data for evaluating pharmacokinetic and pharmacodynamics parameters of antimicrobials, including colistin, the AMS team decided to broaden the responsibilities of the clinical pharmacist and appointed an additional clinical pharmacist (S Sudhir) to the AMS team. This allowed for the gathering of local population data to develop bespoke dosing schedules for antimicrobials such as colistin, allowing for more population-targeted guidelines [ 21 ]. The AMS team, led by the clinical pharmacists and approved by the microbiologist, expanded on the existing hospital antibiogram to develop department and body fluid-specific antibiograms.…”
Section: Methodsmentioning
confidence: 99%